Strategies for improving the competitiveness of agricultural products and China's trade policy in the world market - Mahammad Aliyev; Mushfig Guliyev; Ulmas Abdullaev; Lamiya Huseynova; Gulnara Azizova (Наукові горизонти)
The purpose of the study was to analyse the impact of foreign direct investment (FDI) on China's agricultural sector, with a focus on technology upgrading, productivity improvement and access to new markets. The study empirically assessed the performance of leading agricultural companies such as Joyvio Beidahuang Agricultural Holdings, Zheng Dong, Beijing Capital Agro and Rainbow Agro using statistical data and executive interviews. The results confirmed that FDI significantly contributes to the productivity of the agricultural sector, with a 47.8% increase in yields and a 60% increase in exports. In addition, 60% of the companies were able to successfully enter new international markets by improving product quality and adopting modern technologies. An important aspect of the study was the identification of trade barriers, such as complex certification procedures and strict sanitary requirements, which make it difficult to access international markets. The results also highlighted the need for further improvements in supply chains, government support and innovation to enhance the competitiveness of China's agricultural sector in the global arena. In addition, the analysis shows that the supply chain ecosystem requires Optimisation to allocate resources more efficiently and reduce transportation costs. Finally, the study emphasised the importance of sustainable development and the environment in the context of global challenges, including climate change and food security. Effective cooperation with international partners and the integration of modern production approaches will ensure the long-term stability and development of China's agricultural sector, contributing to a sustainable and secure future for the country's agriculture sector